Policy responses to the COVID-19 pandemic in West Africa: a scoping review protocol - Kathrin Müller; Clare Wenham; Johanna Hanefeld; Hanna-Tina Fischer (BMJ Open, 2023)
Introduction Four years after the devastating Ebola outbreak, governments in West Africa were quick to implement non-pharmaceutical interventions (NPIs) in response to the rapid spread of SARS-CoV-2. The NPIs implemented included physical distancing, closure of schools and businesses, restrictions on public gatherings and mandating the use of face masks among others. In the absence of widely available vaccinations, NPIs were the only known means to try to slow the spread of COVID-19. While numerous studies have assessed the effectiveness of these NPIs in high-income countries, less is known about the processes that lead to the adoption of policies and the factors that influence their implementation and adherence in low-income and middle-income countries. The objective of this scoping review is to understand the extent and type of evidence in relation to the policy formulation, decision-making and implementation stages of NPIs in West Africa.Methods and analysis A scoping review will be undertaken following the guidance developed by Arskey and O’Malley, the Joanna Briggs Institute (JBI) methodology for scoping reviews and the PRISMA guidelines for Scoping Reviews. Both peer-reviewed and grey literature will be searched using Web of Science, Embase, Scopus, APA PsycInfo, WHO Institutional Repository for Information Sharing, JSTOR and Google Advanced Search, and by searching the websites of the WHO, and the West African Health Organisation. Screening will be conducted by two reviewers based on inclusion and exclusion criteria, and data will be extracted, coded and narratively synthesised.Ethics and dissemination We started this scoping review in May 2023, and anticipate finishing by April 2024. Ethics approval is not required since we are not collecting primary data. This protocol was registered at Open Science Framework (https://osf.io/gvek2/). We plan to disseminate this research through publications, conference presentations and upcoming West African policy dialogues on pandemic preparedness and response.